Urban Tourism: An Analysis of Visitors to Istanbul - Ebru Kerimoglu; Hale Ciraci (European Regional Science Association (ERSA), 2006)
Urban tourism study is a research involving the change in the economic base of cities, in the land use of the urban places as well as in the social life's of the residents. The most important issues for the cities taking place within the developing tourism sector are managing the change and the people influenced by such change successfully. The cities, the final spatial products of the activities of the mankind do have a considerable importance on tourism. The cities are the places where cultural inheritance is intense and gathered. Cities are the biggest touristic resources and are themselves among the important destinations. The importance of city destinations has increased with the efforts to ensure tourism variation in Turkey and with the new strategies to extend tourism season to the whole year. These developments increased the expectations of Turkish tourism from Istanbul substantially. The primary goal for Istanbul is looking after its historical, cultural and natural resources and providing the city with a global status, a development in compliance with that of the country and the region, taking place within the other metropols in the global economic development process, making use of the regional opportunities within the economic structures of the world and region and assuming a lead role in this structuring and establishing a protection and development balance as a metropolis with historical, cultural, scientific, artistic, politic, commercial and service backgrounds. For Istanbul's being a global city, its commercial and touristic characteristics should be emphasized and the service sector for that purpose should be developed with planning strategy. This study assumes that the tourism function, considered to be the most efficient means to introduce Istanbul to the rest of the world, should be developed in a planned and strategic manner and intends to analyze the demographic profiles of international visitors visiting Istanbul make strategies to tourism development of Istanbul as well as consider to necessity very detailed studies on the subject.
Keywords: 330